Pre-operative pyuria predicts tumor recurrence in patients undergoing transurethral resection of bladder tumor with post-operative instillation of BCG - Khizar Hayat Gondal; Majed Saeed; Syed Atif Hussain; Rana Atta Ur Rehman; Ali Shandar Durrani; Muhammad Raheem Sajjad (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: In Pakistan, urinary bladder cancer is one of the top ten malignancies. The most important concern after its treatment is tumor recurrence. Recent literature claimed that pre-operative pyuria in patients undergoing transurethral resection of bladder tumor was associated with significantly higher frequency of recurrence. However, there was controversy in existing literature and no such local published material was available which necessitated the present study. To determine the frequency of pre-operative pyuria in patients undergoing transurethral resection of bladder tumor for non-muscle invasive bladder cancer (NMIBC) with post-operative instillation of Bacillus Calmette Guerin (BCG) and to compare the frequency of tumor recurrence in patients with and without pre-operative pyuria. METHODOLOGY: It was a comparative study. This study involved 280 patients of both genders aged between 20-80 years. Pre-operative pyuria was diagnosed if early morning midstream urine specimen showed ≥10 white blood cells/HPF. Outcome variable was frequency of recurrence after 12 weeks of treatment on check cystoscopy. RESULTS: The mean age of the patients was 57.1±8.5 years. There were 236 (84.3%) male and 44 (15.7%) female patients in the study. 155 (55.4%) patients were tobacco smoker. Pre-operative pyuria was diagnosed in 127 (45.4%) patients while tumor recurrence was observed in 183 (65.4%) patients. The frequency of tumor recurrence was significantly higher in patients with pre-operative pyuria (85.8% vs. 48.4%; p<0.001). CONCLUSION: Pre-operative pyuria was a frequent finding in patients with non-muscle invasive bladder tumor and was associated with higher frequency of tumor recurrence which warrants routine screening of such patients for pyuria and increased frequency of tumor recurrence.